Study of Certain Classes of Multivalent Functions Associated With Integral Operators - et. al., T.G.Thange, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the given article we studied the class Y+ ( of multivalent functions with integral operator. We obtained necessary and sufficient condition for the functions in the class. Several geometric properties like coefficient bounds, closureness property, and integral mean are part of discussion. Extensions of the given class with several results are also pointed out. Mathematics subject classification. 30C45.